Women, Work, and Protest : a Century of U.S. Women's Labor History. - Milkman, Ruth (Routledge library editions. Women's history., 2013)
As paid work becomes increasingly central in women's lives, the history of their labor struggles assumes more and more importance. This volume represents the best of the new feminist scholarship in twentieth-century U.S. women's labor history. Fourteen original essays illuminate the complex relationship between gender, consciousness and working-class activism, and deepen historical understanding of the contradictory legacy of trade unionism for women workers. The contributors take up a wide range of specific subjects, and write from diverse theoretical perspectives. Some of the essays are c.